Kartagener Syndrome: Congenital Variety of Primary Ciliary Dyskinesia with Infertility - Dwivedi, Amit Nandan Dhar (Asian Journal of Medical Sciences, 2010)
We report a rare case of Kartagener's Syndrome, congenital variety of Primary Ciliary Dyskinesia (PCD) with infertility. The patient exhibited the classical triad of which was elucidated by Manes Kartagener in 1933. The frequency of KS in the United States is 1 case per 32,000 live births. Situs inversus occurs randomly in half the patients with PCD; therefore, for every patient with KS, another patient has PCD but not situs inversus. Current nomenclature classifies all congenital ciliary disorders as PCDs in order to differentiate them from acquired types. KS is part of the larger group of disorders referred to as PCDs. Approximately one half of patients with PCD have situs inversus and, thus, are classified as having KS. Keywords: Immotile cilia syndrome; Primary ciliary dyskinesia (PCD); Situs inversus; Chronic sinusitis; Bronchiectasis. DOI: 10.3126/ajms.v1i1.2605 Asian Journal of Medical Sciences Vol.1(1) 2010 p.16-17